A microbial agent effectively reduces ammonia volatilization and ensures good maggot yield from pig manure composted via housefly larvae cultivation - Zhu, Fengxiang; Hong, Chunlai; Wang, Weiping; Lyu, Haohao; Zhu, Weijing; Xv, Hanjing; Yao, Yanlai (Journal of cleaner production, 2020)
Ammonia volatilization is a serious concern in the two-stage composting of pig manure. To reduce ammonia volatilization, an optimal microbial agent concentration for maintaining nitrogen in compost was determined. The microbial agent had a negative effect on housefly larval growth, but all treatments achieved good yields of late-instar maggots above 12% fresh material weight. The volatilization of ammonia was efficiently reduced by directly mixing 1% microbial agent into the initial material, and the ammonia volatilization within the monitoring time was decreased by 60.7% and 68.2% in T3 (undiluted microbial fermentation liquid) and T2 (10-fold diluted microbial fermentation liquid) on day 4, respectively, compared with that of T0 (the same volume of water without microbial agent). The total nitrogen loss from fermentation in T3 was reduced by 44.76% by day 6 compared with that in T0 but decreased only by 17.12% upon the completion of composting. Maggot breeding had a substantial effect on the microbial population structure in the materials. According to the changes in the total organic carbon content, soluble carbon content, and seed germination index, the composting process should be completed within 3–4 w to retain optimal organic carbon and nitrogen contents. Our results highlight that the microbial agent beneficially not only reduces ammonia volatilization and the total nitrogen loss but also ensures good maggot yield from pig manure composted via housefly larvae cultivation. [Display omitted] •A yield of maggots above 12% fresh material weight was achieved for all treatments.•The ammonia volatilization was decreased by 68.2% on day 4 with microbial agent.•Directly mixing the microbial agent into the raw material was more effective.•Microbial agent reduced nitrogen loss for 44.76% in the maggot cultivation stage.•Two-stage composting should be finished in 3–4 w to retain carbon & nitrogen.